ANALISIS CUSTOMER SATISFACTION KUALITAS PELAYANAN DI BANK SYARIAH INDONESIA (BSI) KCP. BENGKULU ARGAMAKMUR - Yunita Sri Lestari; Asnaini; Debby Arisandi (Universitas Muhammadiyah Bengkulu, 2023)
The purpose of this study was to determine customer satisfaction at Indonesian Islamic banks KCP. Bengkulu Argamakmur and to find out the form of Indonesian Islamic bank KCP services. Bengkulu Arga Makmur. This research method is a field research (field research). Sources of data used in this study are primary data and secondary data. Collecting data using interviews, documentation, and observation. The data analysis technique used is data reduction, data display and conclusion drawing/verification. The results of this study indicate that the services available at Bank Syariah Indonesia KCP. Bengkulu Arga Makmur provides satisfaction for customers. This is shown through 5 (five) factors, namely: tangible (physical evidence) in the form of office locations and waiting room facilities are points of great concern. Reability (reliability) ease of service procedures such as banking transactions provided quickly and precisely. Responsiveness is provided through a responsive response to customer needs, helping customers who have difficulty filling out slips, directing customers to units that suit customer needs. Assurance consists of several components such as communication, credibility, security, competence and courtesy. Empathy (empathy) gives attention by trying to understand the wishes of customers.